Psychological Impact of Maxillectomy and Prosthodontic Rehabilitation and Role of Socio-demographic and Disease-related Variables - Chanchal Gupta; Ruchi Raj (Journal of Cancer Research and Practice)
Background: The objectives of this study were to evaluate the psychological impact of maxillectomy and prosthodontic rehabilitation and to assess the role of various sociodemographic and disease-related variables on the psychological distress of patients. Materials and Methods: Thirty-nine patients who were referred for prosthodontic rehabilitation after maxillectomy were enrolled, of whom 36 completed the study. The Hospital Anxiety and Depression Scale (HADS) was used to assess and compare the psychological distress level after maxillectomy (T0) and 3 weeks after insertion of a definitive obturator (T1). The Obturator Functioning Scale was also used to assess the functioning of the obturator prosthesis. The means of anxiety and depression scores were also compared among different variables using one-way ANOVA. A probability level of P < 0.05 was considered statistically significant. Results: Anxiety and depression scores were significantly reduced at T1 compared to T0 (P < 0.001). The patients reported little or no difficulty with the obturator prosthesis. Among the sociodemographic variables, psychological distress was not affected by the patient’s age or marital status at any time point (P > 0.05); however, the female, illiterate, and unemployed patients had significantly higher HADS scores compared to the male, graduate, and employed patients (P < 0.05). Malignant tumors and large postsurgical defects had a significant impact on psychological distress compared to benign tumors and small defects (P < 0.05). Conclusion: Maxillectomy had a profound psychological impact. Prosthodontic rehabilitation after maxillectomy restored function and esthetics to near normalcy, and this helps to cope with psychological distress.